2008
DOI: 10.1148/radiol.2483071927
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous MR/PET Imaging of the Human Brain: Feasibility Study

Abstract: The purpose of this study was to apply a magnetic resonance (MR) imaging-compatible positron emission tomographic (PET) detector technology for simultaneous MR/PET imaging of the human brain and skull base. The PET detector ring consists of lutetium oxyorthosilicate (LSO) scintillation crystals in combination with avalanche photodiodes (APDs) mounted in a clinical 3-T MR imager with use of the birdcage transmit/receive head coil. Following phantom studies, two patients were simultaneously examined by using flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
348
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(360 citation statements)
references
References 15 publications
1
348
0
11
Order By: Relevance
“…The resolution of the reconstructed images was 2.5 mm FWHM at the centre and 4.5 mm at 10 cm offaxis with a sensitivity of 5.6%. Overall, the quality of the images was comparable to that of the corresponding standalone PET and MRI systems [16].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The resolution of the reconstructed images was 2.5 mm FWHM at the centre and 4.5 mm at 10 cm offaxis with a sensitivity of 5.6%. Overall, the quality of the images was comparable to that of the corresponding standalone PET and MRI systems [16].…”
Section: Introductionmentioning
confidence: 72%
“…Schmand et al demonstrated for the first time that simultaneous PET and MR data acquisition is feasible with an integrated PET/MR tomograph [15]. Figure 3 shows the first simultaneously acquired MR and PET images [16] in a volunteer and demonstrates the feasibility of combined MR and PET data acquisition without significant interference between the two modalities. Conventional MR imaging on a 3-T MR tomograph was performed using a T2-weighted turbo-spin echo sequence, a fluid attenuated inversion recovery sequence and a 3-D T1-weighted fast low-angle shot sequence.…”
Section: Introductionmentioning
confidence: 98%
“…The BrainPET was operational at a limited number of sites, but the design was space limited and did not allow for a full range of neuroimaging options. The utility of the instrument was demonstrated (Schlemmer et al, 2008), particularly for neuro-oncology (Heiss et al, 2011). Figure 2 shows examples of simultaneous imaging in tumor patients and the suitability of hybrid imaging for monitoring of disease progression, treatment response, and fMRI assessment of motor function (Herzog et al, 2011).…”
Section: Simultaneousmentioning
confidence: 99%
“…Efforts by Hasegawa and colleagues in the late 1980s paved the way for combined SPECT/CT (in 1996) and PET/CT (in 1998) platforms for human imaging that generally facilitated sequential data acquisitions with high spatial correspondence of the multimodality data (Townsend, 2008). Simultaneous PET/MRI is now possible in humans (Catana et al, 2008;Herzog et al, 2011;Schlemmer et al, 2008) after an extensive technical development period that includes early study of magnetic field effects on positron range (Christensen et al, 1995;Iida et al, 1986) and subsequent development of a preclinical simultaneous PET/MR scanner by Cherry and colleagues (Townsend, 2008, for review). In the preclinical animal imaging arena, multimodality molecular imaging has been widely applied with dual and triple modality options (i.e., PET/MR, PET/SPECT/CT, or SPECT/CT/optical) possible or under development (Goorden and Beekman, 2010;Stout and Zaidi, 2009;Wehrl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While virtually all commercially available clinical and hybrid imaging systems have been configured in the form of SPECT/CT [8] or PET/CT [9], combined PET/MR scanners [10,11] allowing for simultaneous (as opposed to sequential scanning for the above-mentioned systems) clinical wholebody imaging following the successful design of a brain dedicated prototype [12] are being designed taking advantage of significant financial support from European and North American funding agencies targeting these particular technologies. In this respect, there are clear indications that several manufacturers are focusing their efforts on the development of various designs of MR-compatible wholebody PET systems.…”
mentioning
confidence: 99%